Collective excitations in dynamics of liquids: a "toy" dynamical model for binary mixtures - Bryk, T.; Mryglod, I.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We propose a new «toy» dynamical model that permits us to derive analytical expressions for dispersion of two branches of «bare» propagating collective excitations in binary disordered systems in the whole range of wavenumbers. These expressions are used for the analysis of dependence of dispersion curves on mass ratio and concentration at fixed density of the system. An effect of hybridization of two branches is discussed in terms of mode contributions to time correlation functions. This allows us to estimate the regions with dominant types of coherent or partial dynamics.